A Prototype of An Automated Farm Monitoring System - Jegede, Abayomi; Shanding, Gershinen; Thomas, Godwin (My University, 2021)
The utilization of technology in farming requires a deep understanding of agricultural processes, biology, chemistry, and empirical knowledge. Several parameters are considered and thoroughly investigated when designing a system to support improved, efficient and sustainable farming procedures. The aim of this paper is to propose a prototype of a system for real-time monitoring of environmental and climatic parameters (such as temperature, humidity and soil moisture) in order to provide farmers with accurate, reliable, and on-demand information necessary to make informed decisions. The paper presents the functional requirements, non-functional requirements, block diagram and schematic hardware diagram of the proposed farm monitoring system. A topdown approach is used to design the architectural diagram and the system flowchart. The proposed system is implemented on a Raspberry PI board. It uses the google maps API and the darksky API to obtain the location information (longitudinal and latitudinal coordinates) of the farm environment. Tkinter is used to implement the graphical user interface, while SQL is used to implement the database for storing information collected by the sensors. The environmental and climatic parameters are collected using sensors installed on the farm. The information collected is logged into a database for storage and further processing and analysis by various components of the proposed farm monitoring system. The results of the analysis provide farmers with the information required for accurate, reliable and timely decision making
Keywords: automated agriculture; farm monitoring; IoT; smart sensor; WSN